2012
DOI: 10.1155/2012/908562
|View full text |Cite
|
Sign up to set email alerts
|

Hesperidin-3′-O-Methylether Is More Potent than Hesperidin in Phosphodiesterase Inhibition and Suppression of Ovalbumin-Induced Airway Hyperresponsiveness

Abstract: Hesperidin is present in the traditional Chinese medicine, “Chen Pi,” and recently was reported to have anti-inflammatory effects. Therefore, we were interested in comparing the effects of hesperidin and hesperidin-3′-O-methylether on phosphodiesterase inhibition and airway hyperresponsiveness (AHR) in a murine model of asthma. In the present results, hesperidin-3′-O-methylether, but not hesperidin, at 30 μmol/kg (p.o.) significantly attenuated the enhanced pause (P enh) value, suppressed the increases in numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Few studies demonstrated that HSP protected the organ tissues against various toxic agents, which induced oxidative damage such as TCDD, cadmium, and dimethylbenzanthracene [23,24]. Different mechanisms have been suggested for the beneficial effects of HSP against LPS damage including its antioxidant ability or suppression of AhR receptors in the cells [25].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies demonstrated that HSP protected the organ tissues against various toxic agents, which induced oxidative damage such as TCDD, cadmium, and dimethylbenzanthracene [23,24]. Different mechanisms have been suggested for the beneficial effects of HSP against LPS damage including its antioxidant ability or suppression of AhR receptors in the cells [25].…”
Section: Discussionmentioning
confidence: 99%
“…However, HP prevents the oxidative effects of TCDD and these protective effects are mainly due to its antioxidant properties such as being a scavenger of free radicals or an inhibitor of bio-molecule oxidation. Also, Yang et al [25] have claimed that HP suppressed the AhR receptors, thus the beneficial effects of HP against TCDD toxicity may be partially accounted for by the suppression of these AhR receptors. The present study demonstrated that TCDD treatment caused severe histological damage (eosinophilic-stained and pyknotic nuclei cells, congestion, intracytoplasmic vacuolization and cell infiltration) in liver tissues of rats.…”
Section: Figurementioning
confidence: 99%
“…It was claimed that these effects of HP were due to its suppression of the AhR receptors. It was also determined that [25] Q binds directly AhR as a natural ligand. In this context, the immunoprotective effects of HP in TCDD toxicity may occur because Q and TCDD bind AhR competitively.…”
Section: Figurementioning
confidence: 99%
“…Several studies show potential roles of natural plant extracts and compounds for the treatment of asthma and COPD [22,23]. Anti-inflammatory and antioxidant polyphenols including resveratrol, curcumin, quercetin, sulforaphane, lycopene, mangiferin, and dihydroquercetin suppress experimental pulmonary fibrosis and modulate various biochemical features of COPD [24,25].…”
Section: Introductionmentioning
confidence: 99%